The Relationship Between the Executive and Legislative Branches in Regional Financial Governance: An Analysis of the Roles of the Governor and the Provincial Parliament (DPRD): Relasi Eksekutif dan Legislatif dalam Tata Kelola Keuangan Daerah: Analisis Peran Gubernur dan DPRD Provinsi - Rum, Jalaluddin; Mahfudz, Mahfudz; Kalsum, Ummi (IAIN Kendari, 2025)
This study aims to analyze the role of the Governor as the budget executor in influencing the performance of members of the Regional House of Representatives (DPRD) of Southeast Sulawesi Province. The research method employed is descriptive qualitative, using a literature/media documentation approach, in-depth interviews, and budget document analysis. Data were collected from local government financial reports, as well as the perspectives of DPRD members and executive officials. The findings indicate that: (1) the performance of DPRD members of Southeast Sulawesi Province in budget-related matters is influenced by the timeliness of discussions in accordance with the schedule, the quality of oversight, responsiveness, accountability, and coordination with the Governor as the budget executor; (2) there is a lack of technical capacity among council members in “reading” complex financial reports; and (3) the executive branch still tends to play a dominant role as a governmental partner.